Criminal woman, the prostitute, and the normal woman - Lombroso, Cesare 1836-1909; Ferrero, Guglielmo 1871-1942 (Duke University Press, 2012)
The normal woman -- Female criminology -- Pathological anatomy and anthropometry of criminal woman and the prostitute -- Biology and psychology of female criminals and prostitutes